O vídeo como linguagem no estudo da paisagem: experiências e práticas educativas no bairro do Alecrim - Natal/RN - Roberto, Marcelo Rodrigues (2019)
Landscape is one of the most fundamental concepts on Geography. Concerning education, landscape is a content/concept that grows throughout the school life and intensifies the unfolding of meanings, integrating the construction of students’ knowledge on Geography. Therefore, this study addresses the video language as a way to consolidate the teachinglearning process on landscapes, considering the fact that such language is so present in the daily lives of students and teachers and its rapid technical progress and large scope with the popularization of cinema enable, especially youngsters, to be protagonists in such language as producers and broadcasters of audiovisual products. Considering such scenario, it is questioned how cell phones and their digital cameras have been transforming habits, cultures and teaching-learning methods that are occurring in both school and youngsters' culture. Thus, a question arises: How does video language enable geography teachers to adopt educational methods in the construction and sharing of spatial knowledges? Based on such questioning, this study is organized as follows: At first, a study on the concept of landscapes and its reverberations on Geography teaching in a pre-established educational context (Instituto Padre Miguelinho, a centenary public high school located in the district of Alecrim – Natal, RN, Brazil). Afterwards, a theoretical and technical study was performed on the video language that was employed as theoretical background for conducting workshops of video and audiovisual experimentations with a group of senior students of Instituto Padre Miguelinho. Such workshops focused on the studies of geographic landscapes of Alecrim (district where Instituto Padre Miguelinho is located in and which is filled with memories, history, culture, places, routines and life trajectories meaningful for the study of landscapes by the students). At last, a critical analysis was conducted on the teaching-learning process in the application of interviews and conversations related to experimentation process, students’ impressions on the understanding of the concept of landscape and the video exhibition that occurred at the Arts Fair of the Instituto Padre Miguelinho. As a final product that strengthens the theoretical study, this dissertation addresses the Video Language Workshop of the video produced by the students, which is titled “Praça Gentil Ferreira”.